Hemangiosis carcinomatosa as an independent risk factor for long-term survival in Non-Small Cell Lung Cancer patients. (August 2022) - Heldwein, Matthias; Menghesha, Hruy; Doerr, Fabian; Schlachtenberger, Georg; Günther, Aldisa; Polegenko, Evgenija; Amorin Estremadoyro, Andres; Quaas, Alexander; Bennink, Gerardus; Wahlers, Thorsten; Hekmat, Khosro
Abstract: Objectives: Recent studies have shown that blood vessel invasion (V1) influences the long-term survival of patients with Non-Small Cell Lung Cancer (NSCLC). The aim of the present study was to emphasize V1 as an independent risk factor. We evaluated the effects of V1 on the survival of NSCLC patients with UICC stages I, II, and III after surgery. Methods: This retrospective study includes 747 consecutive patients with NSCLC who underwent anatomic resection and radical lymphadenectomy at our institution between January 2012 and December 2020. V1- were compared to V0-patients (no blood vessel invasion). All patients received adjuvant therapy according to European guidelines when indicated. After excluding patients with detection of lymphangiosis carcinomatosa, tumor-cells at the resection margin, distant metastases and those, that received neoadjuvant therapy, 1-, 3- and 5- year survival rates were assessed by Kaplan-Meier method. To proof V1 as an independent risk factor, a propensity score matched (PSM) analysis was performed regarding age, gender, UICC-stage, lymph-node involvement, and comorbidities. Results: A total of 461 patients (V0: 440; V1: 21) were included in this analysis. Baseline characteristics did not show any significant difference. Mean age in V0-group was 65.7 ± 10.5 years and 64.1 ± 8.6 years in V1-group (p-value = 0.5). In the V0-group 54.8% were male, whereas in the V1-group this number was 66.7% (p-value = 0.37). Mean survival in V1-group was significantly shorter compared to V0-group (V1: 45.8 ± 9.3 months; V0: 81.1 ± 1.1 months; p-value<0.001). This was confirmed after applying a propensity score matched analysis (V0: 99.9 ± 4.9 months; V1: 45.8 ± 9.3 months; p-value<0.001) - V1 is a prognostic marker independent of UICC stage. The 1-, 3- and 5-year survival rates were significantly shorter for V1-patients (1-year: V0: 100%; V1: 70.6%; p-value = 0.012) (3-year: V0: 95.2%; V1: 46.2%; p-value = 0.002) (5-year: V0: 90.5%; V1: 36.4%; p-value = 0.003). Conclusion: As we have shown with our investigations, V1 has a major impact on long-term survival in NSCLC patients and furthermore, acts as an independent risk factor. Due to our small but specified sample size, our statement should be confirmed by a multicenter study. In the meantime, we suggest making the implementation of the V0/V1 specification mandatory in the tumor classification. Graphical abstract: a. Visual abstractKey question: Does blood vessel invasion have an impact on long-term survival in Non- Small Cell Lung Cancer (NSCLC) patients?Key findings: NSCLC patients with blood vessel invasion show significantly worse 1-, 3- and 5- year survival rates.Take home message: Blood vessel invasion in NSCLC is an independent risk factor for long-term survival rates.b. Central image. Image 1 Highlights: Lung cancer therapy is determined by tumor-size, lymph-node- and distant metastasis. Spreading pattern and lymph node involvement may necessitate adjuvant therapy. Blood vessel invasion has already been associated with worse outcome. Blood vessel invasion represents an independent risk factor for long-term survival.